The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1007/s11244-005-3839-8
|View full text |Cite
|
Sign up to set email alerts
|

Photoreduction of Carbondioxide on Surface Functionalized Nanoporous Catalysts

Abstract: Nanoporous photocatalysts have been designed to exhibit unique photocatalytic activities through framework substitution of titanium species or surface immobilization of rhenium complex onto mesoporous silica. This article summarizes recent work on the synthesis, characterization and photocatalytic activities of the designed porous photocatalysts performed by the present authors. Various spectroscopic investigations revealed that the photo-excited states of these catalysts play a vital role in the photocatalyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 34 publications
1
60
2
1
Order By: Relevance
“…Since this time, research has largely focused on the exploration and development of new semiconductor photocatalysts (23), modifications of the semiconductor catalyst in the form of added cocatalysts, e.g., Ni, Cu, Ag, and Pt (23)(24)(25), new methods to nanostructure the catalyst (26), and the coupling of molecular dyes and cocatalysts with the heterogeneous catalyst (27,28). Whereas these advances have led to improvements in catalytic efficiency and quantum yields, little progress has been realized in extending the selectivity of the reaction to favor the more desirable, higher carbon number liquid hydrocarbons (29).…”
mentioning
confidence: 99%
“…Since this time, research has largely focused on the exploration and development of new semiconductor photocatalysts (23), modifications of the semiconductor catalyst in the form of added cocatalysts, e.g., Ni, Cu, Ag, and Pt (23)(24)(25), new methods to nanostructure the catalyst (26), and the coupling of molecular dyes and cocatalysts with the heterogeneous catalyst (27,28). Whereas these advances have led to improvements in catalytic efficiency and quantum yields, little progress has been realized in extending the selectivity of the reaction to favor the more desirable, higher carbon number liquid hydrocarbons (29).…”
mentioning
confidence: 99%
“…Very recently, it was reported that the selectivity for photoreduction of CO 2 can be tailored by controlling the band structure of a g-C 3 N 4 photocatalyst [287]. Thus, it is clear that the band structure, surface state and sites (e.g., the chemistry of CO 2 adsorption, oxygen vacancies, isolated Ti-species, acidbase properties and the hydrophobic-hydrophilic nature) played very crucial roles in the photoinduced activation of CO 2 [39,88,[288][289][290].…”
Section: Important Factors Affecting Co 2 Activationmentioning
confidence: 99%
“…Yet, the microporous structure of zeolites is not beneficial for the improvement of photocatalytic activity. Thus, a variety of mesoporous molecular sieves (MCM-41, MCM-48, KIT-6, FSM-16 and SBA-15) are also applied in photocatalytic CO 2 reduction [285,290,295,[304][305][306][307][308][309]. Ti-MCM-41 and Ti-MCM-48 mesoporous zeolite catalysts exhibited high photocatalytic reactivity for the reduction of CO 2 with H 2 O at 328 K to produce CH 4 and CH 3 OH in the gas phase.…”
Section: Developing Mesoporous Photocatalystsmentioning
confidence: 99%
“…Inoue et al (1979) were the first to report the photocatalytic reduction of CO 2 in aqueous solutions to produce a mixture of formaldehyde, formic acid, methanol and methane using various wide-band-gap semiconductors. Since then, intensive efforts have been focused on the photochemical production of fuels by CO 2 reduction using a variety of photocatalysts (Halmann 1993;Hwang et al 2005;Indrakanti et al 2009;Olah et al 2009). …”
Section: D) Photochemical Production Of Synthetic Fuelsmentioning
confidence: 99%